Comparison of T stage, N stage, multifocality, and bilaterality in papillary thyroid carcinoma patients according to the presence of coexisting lymphocytic thyroiditis. (August 2015) - Park, Jin Young; Kim, Dong Wook; Park, Ha Kyung; Ha, Tae Kwun; Jung, Soo Jin; Kim, Do Hun; Bae, Sang Kyun
Abstract Purpose: This study aimed to assess the relationship between coexisting lymphocytic thyroiditis and T-N stages of papillary thyroid carcinoma (PTC) by histopathological analysis. Materials and methods: The study included 653 patients who underwent thyroid surgery for PTC at our hospital. Each case was classified as either Hashimoto's thyroiditis (HT), non-Hashimoto type of lymphocytic thyroiditis (NHLT), or normal according to the histopathology of thyroid parenchyma. Patient age, gender, surgical modality, location, T stage, N stage, multifocality and bilaterality were compared according to the histopathology. Results: The prevalence of coexisting lymphocytic thyroiditis was 25.8% (169/653); HT (7.5%, 49/653) and NHLT (18.3%, 120/653). There were no significant differences in T stage, N stage, multifocality and bilaterality with regard to coexisting lymphocytic thyroiditis, regardless of whether HT and NHLT were considered collectively or discretely. Primary tumor size (p < 0.0001), location (p = 0.0011), N stage (p < 0.0001), multifocality (p < 0.0001) and bilaterality (p < 0.0001) differed significantly according to T stage, and gender (p = 0.0193), primary tumor size (p < 0.0001), T stage (p < 0.0001), multifocality (p < 0.0001) and bilaterality (p < 0.0001) differed significantly according to N stage. Conclusions: PTC patients with coexisting lymphocytic thyroiditis did not differ from those with normal parenchyma in terms of T stage, N stage, multifocality and bilaterality.